2019
DOI: 10.20956/ica.v11i1.6400
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF METAL ION Cu (II) and Mg (II) ON THE ACTIVITIES ANTIOXIDANT ANTHOCYANIN OF EXTRACT ETHANOL SKIN DRAGON FRUIT RED(Hylocereuspolyrhizus)

Abstract: The effect of Cu2+ and Mg2+ metal ions on the antioxidant activity of anthocyanins of ethanol extract from the red dragon skin fruit (Hylocereus polyrhizus) has been done. Anthocyanin pigments from ethanol extract the red dragon skin fruit, content and antioxidant activity of anthocyanins from the red dragon fruit skin with ethanol solvent, and the effect of Cu2+ and Mg2+ metal ions on the antioxidant activity of anthocyanins. Identification of anthocyanin was done by identification of color test, using spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The colour test was carried out using HCl 2 M and NaOH 2 M compounds. Concentrated extracts that experienced a steady red change if added HCl 2 M and the colour became green-blue when dripped with NaOH 2 M showed that the extract contained anthocyanins (Sani et al, 2018;Meganingtyas and Alauhdin, 2021;Lestario et al, 2014;Surianti et al, 2019). Discolouration in anthocyanin extracts is associated with the acidic and alkaline conditions of the solution.…”
Section: Colour Change Testmentioning
confidence: 98%
“…The colour test was carried out using HCl 2 M and NaOH 2 M compounds. Concentrated extracts that experienced a steady red change if added HCl 2 M and the colour became green-blue when dripped with NaOH 2 M showed that the extract contained anthocyanins (Sani et al, 2018;Meganingtyas and Alauhdin, 2021;Lestario et al, 2014;Surianti et al, 2019). Discolouration in anthocyanin extracts is associated with the acidic and alkaline conditions of the solution.…”
Section: Colour Change Testmentioning
confidence: 98%